Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1080/13504850701367189
|View full text |Cite
|
Sign up to set email alerts
|

Estimating individual rates of discount: a meta-analysis

Abstract: In this article, we present the results from a meta-analysis conducted over 44 experimental and field studies, which report individual discount rate estimates. We find in our research that the experimental design of a study has a decisive impact on these estimates, and conclude that meta-analysis, in the case of individual discount rates, has a low transfer value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…First, even if it time preference does influence BMI, is not clear whether this relationship can help to explain the trend in BMI as opposed to merely the level. Percoco and Nijkamp (2009) and Borghans and Golysten (2006) 3 A related literature examines the link between risk preference and BMI; see, for instance, Anderson and Mellor (2008). 4 Komlos et al (2004) illustrate a time-series relationship between obesity and both the savings rate and debt-to-income ratio in the US, and also show that developed countries with low savings rates have higher obesity rates.…”
Section: Introductionmentioning
confidence: 99%
“…First, even if it time preference does influence BMI, is not clear whether this relationship can help to explain the trend in BMI as opposed to merely the level. Percoco and Nijkamp (2009) and Borghans and Golysten (2006) 3 A related literature examines the link between risk preference and BMI; see, for instance, Anderson and Mellor (2008). 4 Komlos et al (2004) illustrate a time-series relationship between obesity and both the savings rate and debt-to-income ratio in the US, and also show that developed countries with low savings rates have higher obesity rates.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the experimental elicitation mechanism itself can contribute to differing measured time discount rates as a meta-analysis study has shown (Percoco and Nijkamp 2009). A comparison of close-ended and open-ended time preference elicitation mechanisms showed that close-ended mechanisms elicit lower mean discount rates, although there is consistency between social and private discount rates and between discount rates and individual traits (van der Pol and Cairns 2002).…”
Section: Reviewmentioning
confidence: 99%
“…First, even if time preference does influence BMI, it is not clear whether this relationship can help to explain the trend in BMI as opposed to merely the level, as there is a lack of evidence that time preferences have changed as obesity has been rising. In a meta‐analysis of experimental and field studies on time preferences published from 1978–2002, Percoco and Nijkamp () find no evidence of changing time preferences. Borghans and Golsteyn () examine trends in some of their proxy variables for time preference and find no evidence that individuals have become systematically less patient.…”
mentioning
confidence: 99%